Forging alliances in community and thought - Guadarrama, Irma N.; Ramsey, John; Nath, Janice L. (Research in professional school development., 2002)
This text is divided into four parts: exploring theoretical paradigms in design, development and enactment of PDSs; standard-based teacher education and PDSs; best practices profiles of PDSs that advance understanding of research in the field; and toward a research agenda that strengthens PDSs.